Ecological Implications of Coastal Defence Structures (CDS) in Kuala Nerus, Terengganu (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
Coastal defence structures (CDS) play a significant role in erosion control and flooding risk, hence saving human residences and properties. In Kuala Nerus, Terengganu, the construction of CDS is expanding as erosion never ceases, especially during the northeast monsoon season. However, after the CDS completion, information on the ecological impacts of the structures remains limited. Hence, this study determined the sediment characteristics, total organic matter (TOM) and heavy metal contents, as well as water physical and oceanography parameters in the CDS area in Kuala Nerus, Terengganu. Sampling was conducted from March to December 2021, involving five stations: four representing different CDS types – 1) groyne (G), 2) semi-enclosed jetty-type breakwater (S) and 3) breakwater with tombolo (B) and 4) breakwater without tombolo (T), and 5) a control station. Sediments were collected from both exposed and sheltered stations using a Ponar grab. Results revealed that all stations predominantly consist of very fine sand (St. 3: 23.891% - Control: 75.799%), medium sand (Control: 9.258% - St. 2: 30.160%), and coarse sand (Control: 2.348% - St. 1: 28.593%). The sheltered stations documented higher TOM (average 2.21%). Heavy metal concentrations of lithium, chromium, iron, copper, zinc, cadmium, lead, arsenic, and mercury are within the allowed value for the upper continental crust. Sheltered stations documented lower current speeds and wave heights. Overall, the present study proved that the CDS have significantly altered the sediment characteristics, chemistry and nearshore hydrodynamic condition in Kuala Nerus coastal area, underlying the need for continued ecological monitoring in the modified coastal environment.
Keywords: Coastal defence structures (CDS); Kuala Nerus; Ecological; groyne; breakwater